Resveratrol appears to protect against oxidative stress and steroidogenesis collapse in mice fed high‐calorie and high‐cholesterol diet. (23rd January 2014) - Wang, H.‐J.; Wang, Q.; Lv, Z.‐M.; Wang, C.‐L.; Li, C.‐P.; Rong, Y.‐L.
Summary The detrimental effects on Leydig cells steroidogenesis in mice on high‐calorie and high‐cholesterol diet (HCD) were determined, and the possible protection conferred by resveratrol supplementation was investigated. Male C57BL/6J mice were fed high‐calorie and alone (HCD group) or with resveratrol supplementation (HCD + Res group) for 18 weeks. Male C57BL/6J mice fed standard diet without or with the same dose of resveratrol served as controls. At the end of the experiment, there were significant declines of serum testosterone and luteinising hormone (LH) in HCD group as compared to controls. In line with the hormone alterations, the expressions of StAR and steroidogenic enzymes in testicular tissues were significantly down‐regulated in HCD group. Resveratrol supplementation could significantly improve expressions of StAR and steroidogenic enzymes, and increase serum testosterone and LH concentrations in HCD + Res group. Mice in HCD group also showed a statistically significant down‐regulation in the mRNA expressions of MnSOD and GPx4. Resveratrol supplementation improved testicular MnSOD and GPx4 expression in comparison with HCD group. We propose that resveratrol may attenuate detrimental effects on Leydig cells steroidogenesis in HCD‐fed mice, and its upregulations of antioxidant defence mechanisms and LH level may play a role in its protection. Our data suggest resveratrol appears to have the potential for therapeutic approaches targeting male obesity‐associated secondary hypogonadism.